Penguatan Anti Fraud Awareness Mahasiswa melalui Pembelajaran Pengantar Akuntansi 1 Berbasis Problem Based Learning Models Through Contextual Approach - Elvi Rahmi; Friyatmi Friyatmi; Menik Kurnia Siwi; Erika Takidah; Syahrul Syahrul; Primayaora Oksefa; M Topit Hidayat (Universitas Negeri Padang, 2022)
Good character and awareness are things that are very much needed in carrying out work in various kinds of student professions as future leaders need to have anti-fraud awareness so that later it is hoped that Indonesia will be more honest and clean. Learning. This study aims to increase student fraud awareness through accounting learning using Problem Based Learning Models Through Constextual Approach. This research is a Classroom Action Research study which has a spiral model from Kemmis and Toggart. The research procedure consists of several activity cycles. Which includes the stages of planning (plan), action (act), observation (observe) and reflection (reflection). The data collection instrument consisted of observation sheets, field notes and questionnaires. Data were analyzed using a quantitative descriptive approach using percentages. The results showed that after carrying out 2 cycles of PTK in accounting learning 1, fraud awareness of students was in the very good category with a total score of 90.8